Public Transport Acceptance Among UTHM Undergraduate Students During Pandemic COVID-19 - ZAINURIN, MUHAMMAD FIRDAUS; AHMAD TERMIDA, NURSITIHAZLIN (Recent Trends in Civil Engineering and Built Environment, 2023)
The COVID-19 pandemic has created unforeseen effects in public transportation in cities around the world including Malaysia. Due to rapid spreading of the virus, public transportation is reduced in demand to adhere to the Standard Operation Procedure (S.O.P) and ensure that the public is not infected by the disease. Thus, the objective of this study is to determine university students’ level of acceptance towards public transportation. The number of respondents participated in this online survey was 348 and the respondents are all among Universiti Tun Hussein Onn Malaysia (UTHM) undergraduates’ students. The data collection was done through survey method via an online questionnaire instrument where frequency method was used to analyze the socio-demographic questions. Mean Score Analysis were used to analyze the question regarding to the level of acceptance of students towards public transport before and during the occurrence of COVID-19. All the data was stored and analyzed using Microsoft Excel. The results shows that the acceptance towards public transport before the occurrence of COVID-19 is high while the acceptance towards public transport during the occurrence of COVID-19 is low. An authority should implement a strategy to enhance students to travel by using public transportation to increase the usage of public transport among students and increase the safety and health procedure to provide easiness and to lessen their worried to use public transport due to any infection when using public transport.